مقاصد شریعہ میں حاصل ہونے والے فوائد و تضادات کا تحقیقی جائزہ: A Research Study in the Light of the Maqasid Shari’ah (Purposes of the Shariah), Comparing and Contrasting the Advantages and Disadvantages - Dr Hassan Baig; Hafiza Hafsa Majeed; Hafsa Maqsood (Al Manhal Research Journal, 2024)
This paper aims to explore that an advantage implies goodness. Opportunism is the complete opposite of corruption. Corruption comes from harm. Underhandedness is something contrary to benefit, which alludes to the mischief, that is consistently and frequently to individuals or people. Those that safeguard the reasons for the Sharia are practicality, and those targets that compromise the Sharia are offenses. There are four sorts of advantages and damages. The fundamental standard for recognizing advantages and damages is Sharia. After that is keenness, there are three types of correlation among advantages and damages: comparison of advantages and disadvantages, as well as advantages and disadvantages. As of now, a few issues have emerged in certain Flavors which should be settled, and this examination is vital for this arrangement.